TEACHERS’ ROLES IN EDUCATION MANAGEMENTS: PROBLEMS AND SOLUTIONS IN INSTRUCTION, MANAGEMENT, AND POLITICS AREAS - Kristiyani, Christina; Krisdiyanta, Nugraha (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
It is commonly known that there are some problems of education in schools in Indonesia. One of the problems is related to teachers. Teachers, in education managements, can be the agent of change as well as the implementer of the curriculum. In doing those two roles, there are three areas of responsibilities, namely instruction, management, and politics which relates to the policy made by the teacher in the classroom. This paper is going to underline the problems of the teachers’ roles in those three areas seen from the school practice in Indonesia. Since this research discusses the problems and solutions which relate to ideal conditions and ideas, the research applies the library research. The problems of the teacher’s role are viewed based on experiences by 12 teachers who were from different areas in Indonesia but they were in the same class in PPG (Training on Professional Teachers). The data were taken based on by asking them to tell their own experience related to the three areas. Based on the teachers’ experience, the solution is proposed based on some theories which are related to the problems. Further, it will also put forward the possible solution for those problems. The solutions, of course, are proposed by experts whose theories are employed by this research. The result shows that the solution needs some practical trainings and actions in every policy.